2022
DOI: 10.3389/fpls.2022.849521
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi and Dry Raw Garlic Stalk Amendment Alleviate Continuous Monocropping Growth and Photosynthetic Declines in Eggplant by Bolstering Its Antioxidant System and Accumulation of Osmolytes and Secondary Metabolites

Abstract: Vegetable production under plastic sheds severely threatens regional eco-sustainability via anthropogenic activities (excessive use of agrochemicals, pesticides) and problems associated with replanting. Long-term successive cropping across growing seasons induces continuous cropping stress, whose effects manifest as diminished plant growth. Therefore, it is imperative that we develop environmentally sustainable approaches, such as replacing agrochemicals with vegetable waste like dry raw garlic stalk (DRGS) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
(100 reference statements)
0
11
0
Order By: Relevance
“…The increase in the leaf area when increasing the nitrogen application rate in some cases may be attributed to the weakness of this element and its role in increasing the division of meristematic cells, which is reflected positively on the increase in the size of the vegetative system, including the height of the plant. Ghani et al [ 63 ] also observed that increasing nitrogen fertilizer increased the leaf area of Sorghum bicolor . L. In the present study, sandy loam soil enhanced the leaf area of marjoram plants.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the leaf area when increasing the nitrogen application rate in some cases may be attributed to the weakness of this element and its role in increasing the division of meristematic cells, which is reflected positively on the increase in the size of the vegetative system, including the height of the plant. Ghani et al [ 63 ] also observed that increasing nitrogen fertilizer increased the leaf area of Sorghum bicolor . L. In the present study, sandy loam soil enhanced the leaf area of marjoram plants.…”
Section: Resultsmentioning
confidence: 99%
“…AMF can form extensive hyphal networks in host roots and improve the growth of host plants by promoting nutrient and water uptake [ 85 ]. Additionally, AMF can help to increase chlorophyll synthesis [ 86 ], production of ROS [ 87 ], mineral solubilization [ 88 ], and photosynthesis [ 89 , 90 ] of host plants, thereby reducing abiotic stress. Moreover, AMF can effectively increase the levels of Osmoprotectants in plant leaves and provide potential protection against abiotic stress [ 80 ] and recruit other microorganisms in the soil, thereby altering the rhizosphere microbial environment of the host plants and increasing mineralization [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…APX and CAT act on the same substrate, i.e., hydrogen peroxide but at different sites, with APX eliminating excess hydrogen peroxide from chloroplast while CAT from the cytosol ( Ahmad, 2010 ). Increased APX activity due to crop rotation with leafy vegetables strengthened the key radical scavenging pathways, including ascorbate-glutathione in chloroplasts leading to increased protection of major cellular pathways, including photosynthesis ( Ahanger and Agarwal, 2017a ; Ghani et al., 2022a ). Up-regulation of the activities of APX due to crop rotation prevents the formation of toxic hydroxyl radicals by assisting in the maintenance of redox homeostasis and the electron donors, including ascorbate and glutathione ( Khan and Khan, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eggplant ( Solanum melongena L.) is a valuable vegetable cash crop mostly grown under plastic shed ( Wang et al., 2015 ; Ghani et al., 2022a ). Eggplant production in plastic shed heavily relies on mono-cropping systems.…”
Section: Introductionmentioning
confidence: 99%